Answer:
Explanation:
The given equation is expressed as
(y - b) / (x - 2) = m
We want to express x in terms of m, b and y. The first step is to multiply the left hand side and the right hand side of the equation by (x - 2). It becomes
(y - b) / (x - 2) × (x - 2) = m(x - 2)
(y - b) = m(x - 2)
The next step would be to divide the left hand side and the right hand side of the equation by m. It becomes
(y - b)/m = m(x - 2)/m
(y - b)/m = (x - 2)
The last step would be to add 2 to the left hand side and the right hand side of the equation. It becomes
[(y - b)/m] + 2 = x - 2 + 2
x = [(y - b)/m] + 2